The political economy of Japan (Stanford University Press, 1992)
This is final volume of a series that constitutes an analysis of Japan's phenomenal economic rise, its society, and its place in contemporary world affairs. The papers in these volumes are future-orientated - they raise questions about where Japan is going as it approaches the 21st century...